Effect of microbial load on the level of histamine for some types of domestic and imported red meat during the storage period. - Mohammed, Sudad J. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Histamine is one of the biogenic amines that belong among the naturally occurring substances. It can be formed in food as a result of metabolic processes of microorganisms .If the concentration of histamine is above a normal level (5mg/100g) this could possibly due to bacterial contamination of food harmful affect may occur.Objective: The purpose of this study was to detect histamine forming bacteria and quantification of histamine in fresh meat product available in local meat markets in Baghdad.Methods: Histamine level determination in some red meats product was performed by known colorimetric methods. This method enables a rapid and precise determination of histamine in many samples, in this study, total number of ten red meat were collected from Baghdad local market. Meats were analyzed for histamine. Extraction and determination of histamine in all meat samples were made by colorimetric method. One gram of red meat samples were added to 99ml of sterile peptone water to make dilution 10-1, further dilution was made. 0.1 ml was put to inoculate selective culture media, incubated at 37C for 24 hours. Microbes which have been diagnosed were a Staphylococcus spp. and Pseudomonas spp. by conventional methods.Results: In this study histamine was detected in all red meat samples at concentration ranging from 0.87 to 17.30 mg/100g.Relatively, the histamine level was higher in amber, followed by Al-Hana and Al-murad. Histamine contents were established according to (WHO) regulation. Tested samples contain Pseudomonas spp. and Staphylococcus spp.Conclusions: Regarding the presence of biogenic amines in meat, it also would be useful the study of their role in formation of certain compound in meat and meat products. Contamination of red meat samples with Pseudomonas spp. May be attributed to cross –contamination.